Study of Implementing Affective Evaluation in Islamic Studies Subject at Tapaktuan Primary School 09 - Ali Akbar, Muhammad (Journal of Educational Administration, 2021)
Teachers at Tapaktuan Primary School 09 are required to be able to measure the competencies that have been achieved by students, the teacher must also carry out his duties as a teacher, namely carrying out evaluation of the assignments he gave for a certain time. The results of research on the implementation of affective evaluation at Tapaktuan Primary School 09 are (1) Affective learning outcomes at the receiving level are students at Tapaktuan Primary School 09 realize that discipline must be enforced, laziness and not discipline must be pushed aside. (2). The learning outcomes of the affective domain at the responding level are that students at Tapaktuan Primary School 09 have a growing desire to learn more about Islamic teachings about discipline. (3). The affective learning outcomes at the valuing level are the growth of a strong will in students at Tapaktuan Primary School 09 to apply discipline, both at home, school and in the community because it is based on the belief and judgment that a disciplined life is good. (4). The results of affective learning at the organizational level are that students at Tapaktuan Primary School 09 support the enforcement of national discipline proclaimed by the government. Setting or organizing this is an affective level that is a level higher than valuing. (5). The affective learning result of this last domain is that students at Tapaktuan Primary School 09 already have a unanimous attitude. In reality, students make the commands of Allah SWT in Surat al-'Ashr as a guide for their lives in matters relating to discipline, both at home, school, and in society.